Kepuasan Kerja Karyawan Bagian Fresh Food pada Tiara Dewata Supermarket - RM SATRIO GUMULYA UTOMO; MADE ANTARA; IGA OKA SURYAWARDANI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Employee’s Job Satisfaction at Fresh Food Department Tiara Dewata Supermarket Efforts to obtain optimal performance from the presence of employees in a companyneed to be done by setting the right strategy, namely by thinking about how to manageemployees so that they are able to achieve the company's objectives. This can be realizedby creating job satisfaction of the members of the organization concerned which willfurther improve work performance.The objectives of this research are: (a) To analyze job satisfaction at Tiara DewataSupermarket. (b) To analyze the factors forming employee job satisfaction at TiaraDewata Supermarket. The population in this study were all employees of Tiara DewataSupermarket in the fresh food department with total 60 people. The sample wasdetermined by Saturated Sampling method, which is a sample determination technique ifall members of the population were used as samples. Data analysis method used is factoranalysis, namely The First Order Confirmatory Factor Analysis and The Second OrderConfirmatory Factor Analysis, which is processed using AMOS 22 software.The results show that: (1) Fresh Food employees at Tiara Dewata Supermarket are verysatisfied working under the auspices of the Tiara Dewata Supermarket, this can be seenfrom the results of the average assessment score consisting of: main tasks and workfunctions, supervision by the leadership, opportunities for advancement, co-workers, andworking conditions, with an average overall score of 4.40 at an interval of 4.2-5.0. (2)All research factors and indicators are valid / significant as a measure or form of employee job satisfaction. Overall the factors that give the biggest contribution or thestrongest measure of job satisfaction is the opportunity to progress with the value ofloading factor 0.986, while the factors that give the smallest contribution or the weakestas a measure of the construct of job satisfaction are co-workers with the value of loadingfactor 0.943.